Sama wśród mężczyzn. Zofia Nałkowska jako instytucja życia literackiego w międzywojennej Polsce - Kraskowska, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article presents the role of Zofia Nałkowska in inter-war Polish literary culture. Her activity in the structures of literary life was combined with personal commitment to promotion of young talented authors. While she maintained close bonds with the political elites of the Polish Republic, she also functioned above the ideological divisions, actively supporting authors who were opposed the state. As the only woman she was member of the Polish Academy of Literature. Her participation in the official forms of public life forced her to spend time mostly in male company. At the same time, Nałkowska’s most important relationships, both with women and men, developed in private space.